2007
DOI: 10.1364/oe.15.017681
|View full text |Cite
|
Sign up to set email alerts
|

Optical probe based on double-clad optical fiber for fluorescence spectroscopy

Abstract: We report an optical probe based on a single double-clad fiber (DCF), which is suitable for fluorescence spectroscopy. The excitation light is delivered through the small diameter core of the DCF and the excited fluorescence light is collected by the large diameter inner cladding of the same fiber. To retrieve the signal beam from the inner cladding, we utilize a DCF coupler that couples only the light beams in the inner claddings of two different pieces of DCF. It was found that the separation of the channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…The shape of the tip determines how the light emerging from the fiber is distributed on a tissue sample and also determines the light collection efficiency for viewing the irradiated tissue sample or examining scattered or fluorescing light emitted from the sample. [84][85][86][87][88][89][90][91][92][93][94][95][96] When deciding on the geometry of an optical fiber tip, parameters that need to be evaluated include the sizes of the illumination and light-collection areas, the collection angle (related to the fiber NA), and the fiber diameter. Another important factor to keep in mind is that biological tissue has a multilayered characteristic from both compositional and functional viewpoints.…”
Section: Optical Fiber Biomedical Probesmentioning
confidence: 99%
“…The shape of the tip determines how the light emerging from the fiber is distributed on a tissue sample and also determines the light collection efficiency for viewing the irradiated tissue sample or examining scattered or fluorescing light emitted from the sample. [84][85][86][87][88][89][90][91][92][93][94][95][96] When deciding on the geometry of an optical fiber tip, parameters that need to be evaluated include the sizes of the illumination and light-collection areas, the collection angle (related to the fiber NA), and the fiber diameter. Another important factor to keep in mind is that biological tissue has a multilayered characteristic from both compositional and functional viewpoints.…”
Section: Optical Fiber Biomedical Probesmentioning
confidence: 99%
“…A preform of a conventional SMF is drawn with a conventional fiber drawing tower but the fiber is coated with a low-index polymer instead of a conventional high-index one during the drawing process. Figure 3 shows the cross-sectional schematic and the refractive index profile of the previously reported polymer-clad DCF [24][25], for which UVF PC-409 AP of Luvantix, Korea, was used as the low-index polymer. The diameters of the core, the inner cladding, and the outer cladding were 10 μm, 125 μm, and 250 μm, respectively, in a step index profile.…”
Section: Double Clad Fiber Couplermentioning
confidence: 99%
“…He showed that with a short elongation length the HAF coupler had WDM properties but with a long elongation length it became a high-pass filter. In 2007, L. Wang et al utilized the double-clad optical fiber (DCF) coupler to couple only the cladding modes, not the core mode, of two single mode fibers (SMFs) for the fluorescence spectroscopy [12].…”
mentioning
confidence: 99%
“…Double-clad fiber (DCF) can also provide a common path for the two modalities that ensures co-registration. Additionally, DCF has relatively high AF collection efficiency due to the large inner cladding [33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%